Expression of factors involved in apoptosis and cell survival is correlated with enzymes synthesizing lysophosphatidic acid and its receptors in granulosa cells originating from different types of bovine ovarian follicles - Emilia Sinderewicz; Katarzyna Grycmacher; Dorota Boruszewska; Ilona Kowalczyk-Zięba; Joanna Staszkiewicz; Tomasz Ślężak; Izabela Woclawek-Potocka (BMC, 2017)
Abstract Background Lysophosphatidic acid (LPA) regulates reproductive processes in the cow. Ovarian granulosa cells play a pivotal role in follicle growth and development. Nevertheless, the role of LPA in the local regulation of granulosa cell function in different follicle categories in the bovine ovary has not been investigated. Methods Ovarian follicles were divided into healthy, transitional and atretic categories. The expression levels of AX, PLA2, LPARs and factors involved in apoptosis and cell survival processes in granulosa cells in different types of follicles were measured by real-time PCR. The correlations between the expression levels of AX, PLA2, LPARs and the examined factors were measured. The immunolocalization of AX, PLA2 and LPARs in different ovarian follicles was examined by immunohistochemistry. Statistical analyses were conducted in GraphPad using a one-way ANOVA followed by the Kruskal-Wallis multiple comparison test or a correlation analysis followed by Pearson's test. Results The expression levels of AX, PLA2 and LPARs, with the major role of LPAR2 and PLA2, were found in the granulosa cells originating from different follicle types. The expression levels of the factors involved in cell apoptosis (TNFα and its receptors, FAS, FASL, CASP3, CASP8, β-glycan, and DRAK2) were significantly higher in the granulosa cells of the atretic follicles compared to the healthy follicles. A number of correlations between LPARs, AX, PLA2 and factors associated with apoptosis were observed in the atretic but not in the healthy follicles. A greater expression of the factors involved in differentiation and proliferation in the granulosa cells (DICE1 and SOX2) was found in the healthy follicles in comparison with the atretic. A number of correlations between LPARs, AX, PLA2 and the factors associated with cell survival were observed in the healthy but not in the atretic follicles. Conclusions Granulosa cells are the target of LPA action and the source of LPA synthesis in the bovine ovarian follicle. We suggest that the participation of LPA in apoptosis in the atretic follicles mainly occurs through the regulation of TNF-α-dependent and caspase-induced pathways. In the transitional follicles, LPA might influence the inhibins to shift the balance between the number of healthy and atretic follicles. In the healthy follicle type, LPA, acting via LPAR1, might regulate MCL1 and estradiol-stimulating ERβ mRNA expression, leading to the stimulation of anti-apoptotic processes in the granulosa cells and their differentiation and proliferation.